Pulmonary venous hypertension and mechanical strain stimulate monocyte chemoattractant protein-1 release and structural remodelling of the lung in human and rodent chronic heart failure models. Issue 12 (15th September 2014) - Park, John E S; Lyon, Alexander R; Shao, Dongmin; Hector, Lauren R; Xu, Hua; O'Gara, Peter; Pinhu, Liao; Chambers, Rachel C; Wort, S John; Griffiths, Mark J D
Abstract : Introduction: The burden of chronic heart failure (HF) is rising owing to an increased survivorship after myocardial infarction (MI). Pulmonary structural remodelling in patients with HF may protect against oedema while causing dyspnoea, the predominant symptom associated with HF. The cellular and molecular mechanisms underlying these processes in HF are poorly understood. We hypothesised that pulmonary venous hypertension (PVH) following MI provides a mechanical stimulus for structural remodelling of the lung via monocyte chemoattractant protein-1 (MCP-1). Methods: Human lung microvascular endothelial cells (HLMVEC) and Ea.Hy 926 cells exposed to cyclic mechanical strain (CMS) in vitro were analysed for MCP-1 expression and activation of signalling intermediates. HF was induced in Sprague–Dawley rats 16 weeks after MI; a cohort was rescued with AAV9.SERCA2a gene therapy to reduce PVH. Results: HLMVEC and Ea.Hy 926 cells exposed to CMS upregulated MCP-1 gene expression and protein release in an extracellular-signal-regulated kinase (ERK) 1/2 dependent manner. Supernatants from these experiments stimulated fibroblast (human fetal lung fibroblast -1) and pulmonary artery smooth muscle cell proliferation and differentiation. Total lung collagen, a marker of structural remodelling, and MCP-1 gene expression were increased in the lungs of rats with post-MI HF. SERCA2a gene therapy that attenuated PVH after MI was associated with lower levels of lung collagen and MCP-1 gene expression in the lung. Conclusions: Mechanical strain associated with PVH may stimulate pulmonary structural remodelling through ERK 1/2 dependent induction of MCP-1. These findings provide insights into the pathophysiology of lung remodelling in HF and highlight novel, potential therapeutic targets.